Economic development and complexity: Introduction to special issue - Jo\~ao Basilio Pereima Neto (EconomiA, 2020)
This special issue on Economics Development and Complexity contributes to the economic theory by gathering ten articles each of which presents a different economic problem from a complexity perspective. The articles analyse economic issues such as growth and structural change, macroeconomic policy, international trade, industrial dynamics, and ethnocentrism by using approaches such as agent-based economics, genetic algorithms, non-linear systems and network analysis. These articles were selected among submissions of an open call and participants of the 1st Workshop on Economic Complexity and Development held on 9 and 10 December 2018 in Curitiba, Brazil promoted by Nex-Nucleo of Economics and Complexity (UFPR, Brazil) and SPRU-Science Policy Research Unit (Sussex, UK). Economic development is one of the most complex phenomena that humanity has ever encountered. Its understanding has challenged policymakers, managers, politicians and the scientific community for centuries. At the same time, a growing number of unexpected events has surprised all of us such as the emergence of rumpus around the world (the last one hatching on 20 October in 2019 in Chile), financial crisis (2008), political turns in Europe and USA and Latin American countries in 2017-2019, diffusion of disruptive technologies, and last but not least, the COVID19 outbreak and its disastrous impact on our lives and all world economies. We feel that to understand this kind of emergent phenomena, not only new theories and different tools are needed but also a completely new approach for economic science, an approach based on complexity theory.
Keywords: 330